2010
DOI: 10.1111/j.1365-2648.2010.05288.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of conscience, stress of conscience and burnout among nursing staff in residential elder care

Abstract: Both occupational groups viewed conscience as an asset and not a burden. Registered Nurses seemed to exhibit sensitivity to expectations and demands and nursing assistants used their conscience as a source of guidance in their work. Structured group supervision with personnel from different occupations is needed so that staff can gain better understanding about their own occupational situation as well as the situation of other occupational groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
102
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(117 citation statements)
references
References 43 publications
6
102
0
9
Order By: Relevance
“…On the other hand, avoiding patients or their family members is not a cause of troubled conscience, because healthcare professionals rarely avoid patients or relatives who need their help. Stress of conscience is an important risk factor for burnout in nurses (Glasberg et al, 2007;Juthberg et al, 2010;Saarnio et al, 2012). Theoretically, we should conclude that nurses often suppress their conscience to allow the working process to contin-ue.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, avoiding patients or their family members is not a cause of troubled conscience, because healthcare professionals rarely avoid patients or relatives who need their help. Stress of conscience is an important risk factor for burnout in nurses (Glasberg et al, 2007;Juthberg et al, 2010;Saarnio et al, 2012). Theoretically, we should conclude that nurses often suppress their conscience to allow the working process to contin-ue.…”
Section: Discussionmentioning
confidence: 93%
“…7 One explanation for this inconsistency could be that there might be more occupational differences between nurses and nurse assistants in elderly care, compared to other care settings. Just as in Glasberg et al, 28 the nursing staff characteristics seemed to be unrelated to Stress of Conscience.…”
Section: Discussionmentioning
confidence: 99%
“…Conscience per se can be perceived in different ways, as an asset and guide or a burden. 7 Stress of Conscience has been described as: 'a product of the frequency of the stressful situation and of the perceived degree of troubled conscience as rated by healthcare personnel themselves' (p.636). 6 Studies on Stress of Conscience in psychiatric care are still uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…According to Juthberg et al 17 , psychiatrists, the percentage of high burnout for emotional exhaustion was 21%, depersonalization 12.2%, and low personal accomplishment 72%. In comparison with these previous studies, which used the same cut-off scores as this study, the subjects of this study indicated a high level of burnout.…”
Section: Discussionmentioning
confidence: 99%